2018
DOI: 10.1016/j.wneu.2017.12.081
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Spinal Stabilization without Fusion for Spinal Metastatic Disease

Abstract: Objectives Spinal stabilization surgery is an integral part of the treatment of spinal metastatic disease. Bony fusion is the hallmark of spinal stabilization in non-oncology patients. Spinal oncology patients are unlikely to achieve bony fusion due to their overall prognosis and concurrent therapies. Stabilization surgery without fusion may be a reasonable approach for these patients. Literature evaluating the effectiveness of this approach is limited. The object of this study was to investigate the rate of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…They found that patients with prior or concomitant chest wall resection and a construct length that spanned more than six spinal segments were more likely to experience implant failure leading to revision surgery. In another review by Drakhshandeh et al [12], of 27 patients who underwent separation surgery with posterior spinal decompression and instrumentation without fusion, none developed implant failure in their postoperative follow-up as evidenced on CT scan; thus, no patient required revision surgery. In the review by Bellato et al [13], of 105 patients who underwent spinal decompression and fixation for the treatment of spinal metastases using a posterior approach, without attempted arthrodesis, nine patients (8%) developed implant failure, but none of these patients required revision surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that patients with prior or concomitant chest wall resection and a construct length that spanned more than six spinal segments were more likely to experience implant failure leading to revision surgery. In another review by Drakhshandeh et al [12], of 27 patients who underwent separation surgery with posterior spinal decompression and instrumentation without fusion, none developed implant failure in their postoperative follow-up as evidenced on CT scan; thus, no patient required revision surgery. In the review by Bellato et al [13], of 105 patients who underwent spinal decompression and fixation for the treatment of spinal metastases using a posterior approach, without attempted arthrodesis, nine patients (8%) developed implant failure, but none of these patients required revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The quoted incidence of implant failure after surgery for spinal metastases is approximately 2%-8% [10][11][12][13][14][15]. Patients with implant failure may or may not be symptomatic, and not all patients with implant failure require further revision surgery [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drakhsandeh et al reported no hardware failure in a retrospective series of 27 patients undergoing posterior instrumentation without fusion, while the more reliable 7-years retrospective experience by Amankulor et al that analyzing 318 patients treated with posterior instrumentation without anterior column reconstruction reported 2.8% of hardware failure incidence, while instrumentation longer than 6 levels and chest wall resection resulted to be the risk factors for failure [87] , [88] , [89] . Cofano et al have recently reported no hardware failure in a retrospective series of patients undergoing posterior carbon fiber / PEEK instrumentation, with a mean follow up of 11 months [77] .…”
Section: Evolution In Surgerymentioning
confidence: 98%
“…Of the 17 IF cases, 12 (70.6%) received TES ( Table 2 ), which is similar to that in patients with spinal metastases but significantly lower than that in TES patients reported in other studies. 14 , 15 , 17–20 Park et al reported 15 IF cases (12.1%) in 124 patients with spinal metastasis who underwent corpectomy with instrumentation. 6 Sciubba et al reported IF occurrence in 9 (39.1%) of their 23 patients who underwent TES at the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%